Analisis Persepsi Mobile Learning Readiness Dengan Menggunakan Technology Acceptance Model Dalam Pembelajaran Bahasa Jawa - Pangestu, Sulih Aji; Setyosari, Punaji; Kuswandi, Dedi (Universitas Negeri Malang, 2023)
Technological developments in the current era are growing rapidly. Disruptive innovation from this technological development penetrates human needs in various fields, especially in the field of education. Regulations on technological developments in the field of education become learning innovations to remain effective and efficient in their utilization. The application of Mobile Learning requires a readiness analysis that must be considered from the Perceived Ease of Use and Perceived Usefulness variables. This research is an exploratory study with the technology acceptance model (TAM). The aim is to find out the extent of the level of acceptance of the use of media, especially at the junior high school education level. In the acquisition of overall results data reviewed from several aspects namely Student Readiness, Perceived Ease of Use and Usefulness get very good acceptance from the learners. It is proven that the use of media can be accepted by learners who are in accordance with the needs. Furthermore, it is important for educational institutions and teachers to pay attention to learners' perception of Ease of Use and Usefulness on the use of Mobile Learning. Proper support and provision of relevant and useful content can help learners' readiness level in adopting and utilizing Mobile Learning effectively in the learning process.AbstrakPerkembangan teknologi pada era sekarang yang semakin berkembang pesat. Inovasi secara disrupsi dari perkembangan teknologi ini merambah pada kebutuhan manusia dalam berbagai bidang khususnya dibidang pendidikan. Regulasi pada perkembangan teknologi dalam bidang pendidikan menjadi inovasi pembelajaran agar tetap efektif dan efisien dalam pemanfaatannya. Penerapan Mobile Learning ini membutuhkan analisis kesiapan yang harus diperhatikan dari variabel Perceived Ease of Use dan Perceived Usefulness. Penelitian ini merupakan penelitian eksploratif dengan model penerimaan teknologi (TAM). Tujuan untuk mengetahui sejauh mana tingkat penerimaan pada penggunaan media khususnya di tingkatan pendidikan Sekolah Menengah Pertama. Pada perolehan data hasil keseluruhan ditinjau dari beberapa aspek yakni Student Readiness, Perceived Ease of Use dan Usefulness mendapatkan penerimaan yang sangat baik dari para pebelajar. Hal ini terbukti bahwa penggunaan media dapat diterima oleh pebelajar yang sesuai dengan kebutuhan. Selanjutnya penting bagi institusi pendidikan dan pengajar untuk memperhatikan persepsi pebelajar tentang Ease of Use dan Usefulness pada penggunaan Mobile Learning. Dukungan yang tepat dan penyediaan konten yang relevan dan bermanfaat dapat membantu tingkat kesiapan pebelajar dalam mengadopsi dan memanfaatkan Mobile Learning secara efektif dalam proses pembelajaran.